The Ability of Green Open Spaces in Greenhouse Gas Control to Achieve Green Cities in Kendari City - Hasddin, Hasddin; Muthalib, Abd Azis; Ngii, Edward; Putera, Asrip (International Journal of Energy Economics and Policy, 2022)
The urban challenge in realizing a green city for the purpose of a sustainable city is air pollution resulting from vehicle emissions (Carbon monoxide/ CO2). Reducing vehicle emissions can be done by providing green open spaces. In Kendari City, a potential area for the development of green open space is the Bahteramas General Hospital. Activities in the area and around the Bahteramas General Hospital in Kendari City are quite high so that they contribute to emissions (CO2). The object of research analysis is the number of vehicles (daily traffic), the capacity of electricity use, the area of the Bahteramas General Hospital and the area of the existing green open space. The results showed that the type of vehicle that contributes high to CO2 is a motorcycle. The use of fuel as a source of emission (CO2) which contributes to premium types of greenhouse gases, diesel and the use of electrical energy. The absorption capacity of the existing green open space has not been able to reduce CO2 emissions, so it is necessary to expand the green open space to control greenhouse gases.